PENGARUH PENERAPAN SISTEM E-FILING, SOSIALISASI PERPAJAKAN, DAN TINGKAT KEPERCAYAAN PADA PEMERINTAH TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA JAKARTA SETIABUDI DUA - Atito, Muhammad; Masripah, Masripah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
This study aims to determine whether there is influence from the implementation of the e-filing system, tax socialization, and the level of trust in the government on individual taxpayer compliance at KPP Pratama Jakarta Setiabudi Dua. The research employs a quantitative approach, focusing on individual taxpayers registered and actively engaged with KPP Pratama Jakarta Setiabudi Dua. Employing probability sampling, 150 respondents constitute the sample. The gathered data undergoes analysis via the SEM-PLS method.The results of this study indicate that the implementation of the e-filing system and the level of trust in the government have a positive effect on individual taxpayer compliance at KPP Pratama Jakarta Setiabudi Dua. Meanwhile, tax socialization has no effect on individual taxpayer compliance at KPP Pratama Jakarta Setiabudi Dua.